Minimizing Deadline Misses of Mobile IoT Requests in a Hybrid Fog- Cloud Computing Environment - Omer, Dalia Fatahelrahman (2019)
A Master of Science thesis in Computer Engineering by Dalia Fatahelrahman Omer entitled, “Minimizing Deadline Misses of Mobile IoT Requests in a Hybrid Fog-Cloud Computing Environment”, submitted in May 2019. Thesis advisor is Dr. Raafat Aburukba and thesis co-advisor is Dr. Taha Landolsi. Soft and hard copy available.